Detection of β-Lactamases and Outer Membrane Porins among Klebsiella pneumoniae Strains Isolated in Iran - Ali Hashemi; Fatemeh Fallah; Soroor Erfanimanesh; Parastu Hamedani; Shadi Alimehr; Hossein Goudarzi (Scientifica)
This descriptive study was accomplished on 83 K. pneumoniae strains isolated from two hospitals in Tehran, Iran. Antibiotic susceptibility tests were performed by disc diffusion and broth microdilution methods. ESBLs, MBL, Amp-C, and KPC producing strains were detected by phenotypic confirmatory test, combination disk diffusion test (CDDT), Amp-C detection kit, and modified Hodge test, respectively. OXA-48, NDM-1, and CTX-M-15 genes were detected by PCR and sequencing methods. The outer membrane porins such as OmpK35 and OmpK36 were analysed by SDS-PAGE, PCR, and sequencing methods. From 83 K. pneumoniae isolates, 48 (57.5%), 3 (3.5%), 23 (28%), and 5 (6%) were ESBL, MBL, Amp-C, and KPC positive, respectively. The CTX-M-15 gene was detected in 30 (62.5%) and OXA-48 gene was found in 2 (4.1%) of the 48 ESBL-producing isolates. Two isolates harboured both OXA-48 and CTX-M-15; NDM-1 gene was not detected in this study. Outer membrane porin, OmpK35, was detected in 30 (62.5%) of 48 ESBL-producing isolates while OmpK36 was found in 35 (72.91%) of 48 ESBL-producing isolates. In this study, fosfomycin and tigecycline were more effective than other antibiotics. The high prevalence of β-lactamase-producing K. pneumoniae detected in this study is of great concern, which requires infection control measures including antibacterial management and identification of β-lactamases-producing isolates.